The Encounters in the 21st Century : Polyphony - Emerging Resonances : exhibition guidebook - 21st Century Museum of Contemporary Art, Kanazawa (Kanazawa : 21st Century Museum of Contemporary Art Kanazawa, 2004)
A-POC ; Barney, Matthew ; Briand, Mathieu ; Burden, Chris ; Chalayan, Hussein ; Ciraci, Sarah ; Deki, Yayoi ; Dogane, Yuji ; Eliasson, Olafur ; Erlich, Leandro ; Fabre, Jan ; Fujihata Masaki ; Hatoum, Mona ; Höller, Carsten ; Ishiuchi, Miyako ; Kapoor, Anish ; Kawasaki, Kazuo ; Laing, Rosemary ; Lenzlinger, Jörg ; Lin, Michael ; Milhazes, Beatriz ; Neto, Ernesto ; Orozco, Gabriel ; Oursler, Tony ; Richter, Gerhard ; Rist, Pipilotti ; Ritchie, Matthew ; Steiner, Gerda ; Suda, Yoshihiro ; Tillmans, Wolfgang ; Tuttofuoco, Patrick ; Yanobe Kenji ; Yokoyama, Kow
Engels, Japans
Exhibition. The Encounters in the 21st Century : Polyphony - Emerging Resonances. 21st Century Museum of Contemporary Art Kanazawa. 2004-10-09. 2005-03-21
boek